TEACHING EFFECTIVENESS OF SECONDARY SCHOOL TEACHERS IN EMOHUA LOCAL GOVERNMENT AREA OF RIVERS STATE, NIGERIA - Onyekuru, B. U.; Ibegbunam, Josephat O. (European Scientific Journal, ESJ, 2013)
﻿This study is a descriptive study which investigated teaching effectiveness of secondary school teachers in Emohua Local Government Area. A sample of 80 secondary school teachers from secondary schools in Emohua Local Government Area of Rivers State was involved in the study. Four research questions were answered and three hypotheses tested at 0.05 level of significance. The instrument for data collection was Teacher Effectiveness Checklist, a 29-item instrument which was validated by three experts in the field of Measurement and Evaluation. Its reliability index as determined through test-retest method and Pearson product moment correlation technique was 0.88. The generated data were subjected to SPSS analysis using mean and standard deviation as statistical tools for research questions, and student’s-test for hypotheses. It was found that; (1) teaching effectiveness of teachers from secondary schools in Emohua Local Government Area was below average. (2) Of the variables investigated, teaching experience and teachers’ qualifications had a significant influence on teaching effectiveness of the secondary school teachers while gender had no significant influence. Based on these findings, it was recommended that only qualified and experienced teachers should be recruited to teach in secondary schools located in Emohua Local Government Area. Besides, in-service training should be conducted for teachers to improve on their efficiency or effectiveness in discharge of their duties.